Movement and habitat use of the freshwater catfish (Tandanus tandanus) in a remnant floodplain wetland. Issue 3 (26th June 2014) - Koster, Wayne M.; Dawson, David R.; Clunie, Pam; Hames, Fern; McKenzie, John; Moloney, Paul D.; Crook, David A.
Abstract Knowledge of the movement and habitat use of fishes is important in identifying and understanding the causes of population declines and predicting how populations are likely to respond to management interventions. In this study, radiotelemetry was used to examine the spring and summer movement and habitat use patterns of the freshwater catfish (Tandanus tandanus) in a remnant wetland to inform the development of recovery actions for this threatened species. Twenty‐one adult fish were tagged and released within Tahbilk Lagoon, Victoria, Australia, in September 2009. Fish were located every 1–2 weeks between September 2009 and February 2010, a period which coincides with the spawning period for the species. Eleven of the fish were also tracked every 2 h for 68 consecutive hours in December 2009 to examine diel movements. The study revealed that freshwater catfish make extensive use of cover (e.g. wood and macrophytes) and typically have limited ranges (median total linear range and 90% linear range 599 and 173 m respectively), although they occasionally moved more extensively (up to 1.5 km) between floodplain and riverine habitats. Fish moved over much greater areas at night compared with during the day. There was also evidence of sex‐specific variation in movement, with a trend for greater movement of female fish at night compared with males. The results of the study suggest that strategies that protect macrophyte and wood habitats and improve connectivity between riverine and floodplain habitats are likely to be important in maintaining and restoring remnant populations of this species.